2021
DOI: 10.1016/j.reprotox.2021.08.003
|View full text |Cite
|
Sign up to set email alerts
|

In vitro teratogenicity testing using a 3D, embryo-like gastruloid system

Abstract: Highlights Gastruloids are a new in vitro platform for teratogenicity testing. Teratogens disrupt gastruloid gene expression and morphology with imaging readout. Medium-throughput gastruloid cultures are quantifiable with statistical robustness. Mouse and human gastruloids recapitulate species-specific sensitivities to teratogens. Proof-of-concept as a predictive assay with scope for … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…Gastruloids have been recently proposed as cell-based models for drug safety testing ( Mantziou et al., 2021 ); our findings showing that a commonly used antiasthma drug inhibits gastruloid development, can open the way to further investigate unwanted effects of budesonide treatment on fertility in women. Indeed, partial infertility has been reported in asthmatic women ( Gade et al., 2014 ; Vejen Hansen et al., 2019 ), yet, to our knowledge, the effects of budesonide on pregnancy have not been directly investigated with well-controlled and adequate clinical trials ( Kalola and Ambati, 2021 ).…”
Section: Discussionmentioning
confidence: 71%
“…Gastruloids have been recently proposed as cell-based models for drug safety testing ( Mantziou et al., 2021 ); our findings showing that a commonly used antiasthma drug inhibits gastruloid development, can open the way to further investigate unwanted effects of budesonide treatment on fertility in women. Indeed, partial infertility has been reported in asthmatic women ( Gade et al., 2014 ; Vejen Hansen et al., 2019 ), yet, to our knowledge, the effects of budesonide on pregnancy have not been directly investigated with well-controlled and adequate clinical trials ( Kalola and Ambati, 2021 ).…”
Section: Discussionmentioning
confidence: 71%
“…Beyond genetic causes, congenital heart defects can also be caused by teratogens (e. g. drugs, toxins, metabolites) (Kalisch-Smith et al, 2019). However, no human system exists in which it is possible to investigate, in a high-throughput and easily quantifiable manner, whether teratogens cause compartment- specific defects (Mantziou et al, 2021). Before setting out to test the potential applicability of the cardioid compartment platform in this setting, we first confirmed that a non-teratogenic factor Aspirin (Mantziou et al, 2021; van Meer et al, 2019), at a high 30 μM dosage, did not cause any morphological or significant gene expression differences (Figures S7A, S7A’, and S7B), showing that the cardioid system is not overly sensitive to non-teratogenic drugs.…”
Section: Resultsmentioning
confidence: 99%
“…Human embryo models could also be used to screen for drug toxicity. In a proofof-concept study, Moris has shown that the drug thalidomide -infamous for causing birth defects in humans, but not particularly toxic in mice -had a stronger effect on human gastruloids than on mouse gastruloids, suggesting that these models could be useful for human-specific toxicological screens 15 .…”
Section: Varied Applicationsmentioning
confidence: 99%